VX-765 has a Protective Effect on Mice with Ovarian Injury Caused by Chemotherapy - Lee, Pingyin; Zhou, Canquan; Hu, Xiaokun (Current cancer drug targets, 2023)
Malignant tumors continue to remain a main global public health issue. In the past 40 years, due to strides made in multi-disciplinary comprehensive treatment schemes for patients suffering from malignant tumors, especially chemotherapy schemes, the survival rate has been greatly improved in such patients. This group can be expected to maintain their fertility or have restored endocrine function following successful malignant tumor treatment. Therefore, focusing on the ovarian damage caused by chemotherapy in women of childbearing age is vital in order to protect their fertility and improve their quality of life. This study attempted to evaluate whether VX-765 possesses an ovarian protective effect in ovarian injury induced by chemotherapy in the mice model. Female C57BL/6J mice were administered with VX-765 gavage once a day for 21 consecutive days. Use of cyclophosphamide (Cy) began one week after the last gavage administration of VX- 765. Detailed classification of follicles at various levels was then quantified in each group. Immunohistochemistry and Western blot analysis were then used in order to analyze the expression of key proteins (FOXO3a, mTOR, RPS6 and AKT) as well as their phosphorylation of the PI3K / PTEN / AKT pathways in the ovary. The concentrations of AMH were measured by ELISA. The follicles at all levels of Cy treated mice were less than those of the normal group (P < 0.05). Meanwhile, mice treated with VX-765 prior to receiving Cy treatment had more primordial follicles (PMF) than mice treated with Cy alone (P < 0.05). In early growing follicles (EGF) and antral follicles (AF), no difference was observed among the experimental groups (P > 0.05), however, they were lower than those in the normal group (P < 0.05). In mice treated with continuous Cy, the total follicle number (TF) of mice combined with VX-765 (C-Cy-Vx765) was higher than that of mice without VX-765, and the TF of the two groups was lower than that of the normal group (P < 0.05). The value of PMF/TF in C-Cy-Vx765 group was significantly higher than that in the other three groups, while that of EGF/TF was significantly lower (P < 0.05). Immunohistochemical results showed that the phosphorylated forms of the main proteins of the PI3K / PTEN / AKT pathway were found to be more positive in Cy treated mice. The Western blot analysis showed that when Cy and VX-765 were cotreated, the increased levels of these phosphorylated proteins decreased compared with those treated with Cy alone. The AMH level of infancy Cy and VX-765 co-treated mice was higher than that of infancy normal mice (P < 0.05). After the mice grew to sexual maturity, the AMH level of Cy and VX- 765 co-treated mice was still higher than that of Cy treated mice (P < 0.05), and there was no significant difference with normal mice (P > 0.05). VX-765 can maintain the level of AMH and inhibit the recruitment of PMF, thus protecting mice from Cy induced gonadotropic toxicity. Accordingly, VX-765 may play a protective role in mice with ovarian injury caused by chemotherapy.